Support Pollinators and Boost Farmers' Incomes with Farming with Alternative Pollinators! - Bencharki, Youssef (International Center for Agricultural Research in the Dry Areas, 2024)
Farming with Alternative Pollinators (FAP) boosts crop yield and quality by attracting diverse pollinators and natural pest controllers. This approach integrates marketable habitat enhancement plants (MHEP), nesting, and water support, benefiting farmers in low- and middle-income countries while protecting pollinators.